Implementation of Competence and Motivation in Employee Performance - Tubagus Hedi Saepudin; Rita Mulyanti; Cut Aviyanti (Dinasti International Journal of Management Science, 2023)
The purpose of this paper is to provide insight into how organizations can improve employee performance through effective talent management. This paper uses a qualitative method by finding literature related to the variables in this paper, and implementation. This literature review is to provide an insight and overview of the variables used in this paper. Organizations should allocate resources to build effective motivational mechanisms that can encourage employees to excel, as well as provide training and development initiatives to improve employee competencies. In addition, organizations should invest in establishing efficient leadership styles, fostering a supportive work environment, and assessing the effectiveness of existing training programs to ensure alignment with employee and organizational needs.